Dynamic drags acting on moving defects in discrete dispersive media: From dislocation to low-angle grain boundary. (December 2020) - Kim, Soon; Kang, Keonwook; Kim, Sung Youb
Highlights: The dislocation mobility is determined by how energy dissipates around the moving dislocation core, which results in drag to the dislocation motion. Although the dislocation mobility has been differently expressed depending on the drag mechanisms so far, we suggest a comprehensive theoretical model that describes the dislocation dynamics in general cases. Based on discrete lattice dynamics theory, we prove that the drag effect is generally quantified by two dimensionless group parameters that are defined in this study and that the dislocation velocity can be analytically obtained by solving the 3 rd order polynomial equation. Not only for the dislocations, our model can be applied to describe the motion of low-angle grain boundaries (LAGBs) and further expects unusual behaviors that are not explainable by the continuum theory. All the theoretical derivations are well-supported by molecular dynamics simulations of dislocations and LAGBs. Abstract: Although continuum theory has been widely used to describe the long-range elastic behavior of dislocations, it is limited in its ability to describe mechanical behaviors that occur near dislocation cores. This limit of the continuum theory mainly stems from the discrete nature of the core region, which induces a drag force on the dislocation core during glide. Depending on external conditions, different drag mechanisms are activated that govern the dynamics of dislocations in their own way. This is revealed by the resultant speed of the dislocation. In this work, we develop a theoretical framework that generally describes the dynamic drag on dislocations and, as a result, derive a phenomenological cubic constitutive equation. Furthermore, given that a low-angle grain boundary (LAGB) can be regarded as an array of dislocations, we extend the model to describe the mobility law of LAGBs as a function of misorientation angle. As a result, we prove that both dislocations and LAGBs follow the developed constitutive equation with the same mathematical form despite their different governing drag sources. The suggested model is also supported by molecular dynamics simulations. Therefore, this work has significance for a fundamental understanding of the dynamic drag acting on defects and facilitates a general description of various drag mechanisms.